EVALUASI SALURAN DRAINASE di SEPANJANG JALAN PENGABDIAN sampai JALAN M.YAKUB, KOTA MEDAN, INDONESIA: Analisis Hidrologi Hidraulika dan Evaluasi Kapasitas Saluran Drainase Koridor Jalan Pengabdian – Jalan M. Yakub Kabupaten Deli Serdang - marsella ilevennia br sembiring; alifa yasmin putri; yuni yolanda (Fakultas Teknik Universitas Hamzanwadi, 2026)
This study aims to evaluate the performance of the drainage system along Jalan Pengabdian to Jalan M. Yakub, Percut Sei Tuan District, Deli Serdang Regency. The method used is a descriptive evaluative approach with hydrological and hydraulic analysis, based on rainfall data, population data, and direct field measurements of channel dimensions. The analysis includes runoff discharge calculation using the Rational method, population projection, domestic wastewater discharge estimation, as well as the assessment of sedimentation and evapotranspiration effects.The results show that the existing drainage channels have a total storage capacity of 2.046 m³ per meter length. The total discharge to be accommodated reaches 50.75 m³/s, which is dominated by rainfall runoff of 50.6 m³/s, while the contribution of domestic wastewater is relatively small at 0.153 m³/s. The presence of sediment and suboptimal physical conditions of the channels reduce the effective capacity of the drainage system. In addition, evapotranspiration indicates water loss within the hydrological cycle, although it has a relatively minor effect during high-intensity rainfall events.Based on the evaluation results, several drainage segments are not capable of optimally accommodating the flow discharge, especially during peak rainfall conditions. Therefore, it is necessary to improve channel capacity, conduct routine maintenance, and enhance domestic wastewater management to optimize the performance of the drainage system in the study area.